2021
DOI: 10.3390/children8020083
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Healthy Behaviors and Meeting 24-h Movement Guidelines in Spanish and Brazilian Preschoolers, Children and Adolescents during the COVID-19 Lockdown

Abstract: Background: The aim of this study was to assess changes in physical activity, screen time and sleep duration of preschoolers, children and adolescents and the prevalence of meeting the 24-h movement guidelines during the lockdown caused by COVID-19 in a sample from Spain and Brazil. Methods: A total of 1099 preschoolers, children and adolescents (aged 3–17 years) from Spain (12.1 ± 4.6 years) and Brazil (10.7 ± 4.3 years) were included. An online survey was created and distributed in each country using a snowb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
60
3
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 30 publications
20
60
3
5
Order By: Relevance
“…The actual human health toll will likely be far costlier, particularly considering these estimates do not include the unprecedented changes to human movement patterns that have occurred during the self-isolation and government-mandated physical-distancing measures enacted throughout the COVID-19 pandemic. There is now an abundance of literature investigating how self-isolation affects movement behaviors, including physical activity and sedentary time (3)(4)(5)(6), sleep (7,8), nutrition (6,9), and mental health (10,11), among others. Especially concerning are the dramatic changes to physical activity and fitness reported in the pediatric population (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The actual human health toll will likely be far costlier, particularly considering these estimates do not include the unprecedented changes to human movement patterns that have occurred during the self-isolation and government-mandated physical-distancing measures enacted throughout the COVID-19 pandemic. There is now an abundance of literature investigating how self-isolation affects movement behaviors, including physical activity and sedentary time (3)(4)(5)(6), sleep (7,8), nutrition (6,9), and mental health (10,11), among others. Especially concerning are the dramatic changes to physical activity and fitness reported in the pediatric population (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has also impacted children’s daily routines and functioning [ 24 27 ]. Indeed, changes in children’s sleep routines, levels of screen time, physical activity, and engagement in recreational activities during COVID-19 have been observed [ 28 , 29 ]. Importantly, research has shown that when children experience changes and disruptions in these individual factors, it can precipitate mental health difficulties [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have associated more time in children's sedentary behavior with lower health-related quality of life [1] and poorer mental health outcomes [2]. Furthermore, the recent COVID-19 outbreak forced children around the globe to change their lifestyle, due to social distancing measures, and caused an increase in physical inactivity [3,4]. It is known that regular physical activity may increase life expectancy and play an important role towards the prevention of chronic conditions such as obesity, cardiovascular diseases, and metabolic syndrome [5], and it has unarguable benefits for the health of children [6].…”
Section: Introductionmentioning
confidence: 99%